2021
DOI: 10.1097/mrm.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

mcr-mediated colistin resistance in South America, a One Health approach: a review

Abstract: Antimicrobial resistance is recognized as one of the most important global human health problems in the 21st century. The balance between clinical need and resistance prevention is further compromised by agricultural antibiotic use as some countries have actively used colistin in animal production. Antimicrobial-resistant microorganisms have been found in humans, food, animals, plants, and the environment (water, soil, and air), and they can move between ecosystems. The problem of antimicrobial resistance is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
(139 reference statements)
0
2
1
Order By: Relevance
“…Based on our findings, colistin may be considered a significant therapeutic option for the treatment of CRE, but a prior susceptibility report may be needed. The mcr-1 gene was not detected in any of our isolates, in contrast with the results of other Latin American studies [34][35][36], suggesting that resistance could be mediated by chromosomal mutations or other mcr variants that were not studied and have been described in the region, including mcr-3 or mcr-5 [37][38][39]. Further studies are needed to understand the resistance mechanisms involved in colistin resistance.…”
Section: Discussioncontrasting
confidence: 88%
“…Based on our findings, colistin may be considered a significant therapeutic option for the treatment of CRE, but a prior susceptibility report may be needed. The mcr-1 gene was not detected in any of our isolates, in contrast with the results of other Latin American studies [34][35][36], suggesting that resistance could be mediated by chromosomal mutations or other mcr variants that were not studied and have been described in the region, including mcr-3 or mcr-5 [37][38][39]. Further studies are needed to understand the resistance mechanisms involved in colistin resistance.…”
Section: Discussioncontrasting
confidence: 88%
“…IncFIB, IncFII, IncI2, IncI1, IncFIC, IncFIA, IncX1, and IncX4 were the plasmids with the highest occurrence in animal, human, food, and environmental samples. Moreover, these plasmids have been reported to be associated with HGT for mcr-1 variants and other ARGs ( Ghasemian et al, 2018 ; Daza-Cardona et al, 2022 ). Geographically, there is an apparent homogeneity in the presence of the plasmids IncFIB, IncFII, and IncI2.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in São Paulo, Brazil on KPC-producing K. pneumoniae isolates demonstrated that the polymyxin resistance index varied from 0% in 2011 to 27% in 2015 42 - 44 . Some studies carried out in different Brazilian hospitals have identified strains of polymyxin-resistant enterobacteria, whose responsible mechanisms include modification of membrane LPS through inactivation of mgr B 17 and the presence of the mcr -1 gene 32 , 45 , 46 . Although reports of cases from the USA and Europe are generally rare, an increasing incidence from these regions has been recorded in recent years 47 , 48 .…”
Section: Introductionmentioning
confidence: 99%